Bilateral Subacromial-Subdeltoid Rice Bodies in the Shoulder: A Surgical Case Report - Caroline Rush; Olivia Jochl; Natalie Lowenstein; Jillian Mazzocca; Elizabeth Matzkin (Case Reports in Orthopedics)
Introduction. Rice bodies (RBs) are pale and glossy appearing small fibrinous nodules that form due to synovial or tenosynovial joint inflammation. RBs are significant as they are common in orthopedic practices causing nonspecific symptoms such as pain, swelling, range of motion limitations, crepitus, and catching sensations. These loose bodies occur often within the bursa as a symptom of chronic bursitis and are commonly associated with rheumatoid, inflammatory, or tuberculous arthritis. Reports on RBs are present; however, few bilateral cases within the shoulder appear in the literature. Case Presentation. This case demonstrates an unusual bilateral, subacromial-subdeltoid presentation of rice bodies (RBs) in a 41-year-old Caucasian female patient with a history of rheumatoid arthritis. We describe treatment with right shoulder arthroscopy to remove the loose bodies. One-year postoperative patient-reported outcomes (PROMs) show improvement in symptoms, pain, and overall function. Conclusion. Formation of RBs occurs as a symptom of an inflammatory response in synovial joints. This provokes multiple small fibrin aggregates to collect within synovial bursae and occasionally tendon sheaths. RBs are rarely seen bilaterally. Arthroscopic removal of RBs is an appropriate treatment method for symptom improvement.